Synthesis and Crystal Structure of O-Methyldithiophosphato Nickel Complex [Ni(S2POOCH3)(dppe)] - Li, Yu-Long; Xie, Bin; Zou, Li-Ke; Lin, Xiao (Asian Journal of Chemistry, 2013)
O-Methyldithiophosphato nickel complex [Ni(S2POOCH3)(dppe)] (I) (dppe = Ph2PCH2CH2PPh2) has been synthesized by treatment of (dppe)NiCl2 with (CH2O)2PSSH·Et2NH in THF solution. The new complex (I) was fully characterized by elemental analysis, TGA, IR, 1H, 13C, 31P NMR spectroscopies. In addition the molecular structure of the complex was established by X-ray crystallography. The crystal of [Ni(S2POOCH3)(dppe)] crystallizes in monoclinic, spacegroup P21/n with a = 9.2762(3), b = 17.1214(5), c = 18.8627(6) Å, a = 90.00, b = 96.813(3), g =90.00º, V = 2974.66(15) Å3, Z = 4, C27H27O2P3S2Ni, Mr = 599.23, Dc = 1.338 g/cm3, F(000) = 1240 and μ(MoKa) = 0.976 mm-1. The final R = 0.0521 and wR = 0.1303 for 6073 observed reflections [I > 2s(I)].